Reflections on tourists’ experiential engagement with Scotland’s whisky heritage - Christou, Prokopis A.; Timothy, Dallen J.; Pericleous, Katerina (My University, 2024)
This study investigates how tourists engage with heritage at contemporary experiential sites that have become popular amongst visitors and vital ambassadors of a destination’s heritage. Grounded in the theoretical concept of engagement from an andragogical standpoint, the study utilizes and critically examines reviews from a specific interactive and technologically- advanced whisky experience in Edinburgh, Scotland, namely the Scotch Whisky Experience. Findings expose strong heritage appreciation among visitors, yet challenges exist in engagement despite the optimization of sine qua non human and technologically advanced means. A conceptual diagram of heritage engagement for academic and tourism stakeholders’ consideration is provided, re-enforcing its applicability in contexts beyond the heritage sphere. Theoretical understandings of heritage engagement that ought to be extended beyond visitors’ personal experiential gain and value are also discoursed.
Keywords: Engagement; heritage; netnography; place; tourist experience